THE MULTIPLE ROLE OF FEMALE WORKERS OF POTTERY CRAFTS IN BANYUMULEK, WEST LOMBOK - Aryati, Risma Ade; Emy susanti, Emy susanti (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The phenomenon that occurs in society is that many women help their husbands to earn additional income, besides that women are now able to show their existence in society. This also applies in Banyumulek Village, household women work in pottery but they also have to do domestic work at home. It is interesting to see further how the dual role of women pottery workers. Kediri District, West Lombok Regency.This research method uses a qualitative approach. The subjects in this study were women workers who worked in the pottery industry sector in Banyumulek Village, Kediri District, West Lombok Regency. Data was collected using observation, interview and documentation techniques. The data in this study were analyzed using qualitative data analysis techniques, namely data reduction, data display and drawing conclusions. The study concludes showed Women who work spend more time at work so that time to meet with family members is limited, but this does not make their relationship disharmonious, but instead creates a sense of mutual understanding between family members, especially with their husbands. There is mutual awareness of each other's roles